History of Paleolithic research in the south-eastern massifs of Samarkand region - Ungalov Lazizbek Amiriddin ogli; Bakhranov Abdulla Haydar ogli (Zien Journals, 2024)
This article examines the history of studying ancient Stone Age monuments in the southeastern part of Samarkand, as well as the results of research and the significance of the conducted analyses. The main focus is on the history of investigating Stone Age monuments discovered in the Bulungur district
Keywords: Stone Age monuments; Bulungur; southeastern